Evaluating the therapeutic efficacy, tolerability, and safety of an aqueous extract of Costus speciosus rhizome in acute pharyngitis and acute tonsillitis: A pilot study - Bakhsh, Zainab A. (Saudi Med J, 2015)
OBJECTIVES: To determine the efficacy, tolerability, and safety of an aqueous extract of Costus speciosus (C. speciosus) rhizome in pediatric and adult patients suffering from acute pharyngitis and tonsillitis as an alternative to antibiotics use. METHODS: This pilot cohort trial was conducted at King Abdulaziz University in Saudi Arabia between May and December 2014, among 15 patients with acute pharyngitis and tonsillitis who were administered nasal drops of aqueous extract of C. speciosus rhizome at a dose of 15-30 drops every 8 hours for 3 days. The primary outcome measure was the clinical improvement and remission rate within the first 5 days. RESULTS: The administration of C. speciosus resulted in an improvement in acute symptoms in 60% of the patients treated within the first 24 hours, and remission rate of 93% by day 5, without any recorded adverse effects. CONCLUSION: This study revealed a significant efficacy of the aqueous extract of C. speciosus rhizome in acute pharyngitis and tonsillitis.